Application of Perioperative Nursing Based on Enhanced Recovery After Surgery (ERAS) Principles in Patients Undergoing Total Knee Arthroplasty - Huang J; Wu G; Li X (Therapeutics and Clinical Risk Management)
Juan Huang,1 Guoqing Wu,2 Xiaohong Li1 1Department of Orthopedics, Dazhou Central Hospital, Dazhou City, Sichuan Province, 635000, People’s Republic of China; 2Department of Medical Insurance Management, Dazhou Central Hospital, Dazhou City, Sichuan Province, 635000, People’s Republic of ChinaCorrespondence: Juan Huang, Department of Orthopedics,Dazhou Central Hospital, No. 61 Tongchuan North Road, Tongchuan District, Dazhou City, Sichuan Province, 635000, People’s Republic of China, Email 15181857138@163.comBackground: Enhanced Recovery After Surgery (ERAS) principles have gained widespread adoption in perioperative care to optimize recovery and reduce complications. Total knee arthroplasty (TKA) patients benefit significantly from ERAS-guided strategies, which minimize surgical stress and accelerate postoperative recovery. This study evaluates the application of perioperative nursing care based on ERAS principles and its impact on TKA patients.Methods: A retrospective analysis was conducted on prospectively maintained data of 312 patients who underwent TKA between January 2023 and December 2023. Of these, 158 patients received perioperative nursing care based on ERAS principles, while 154 received standard nursing care. The ERAS-based perioperative nursing protocol included preoperative education, intraoperative fluid optimization, postoperative pain management, and early mobilization strategies. Clinical data, including postoperative complications, length of hospital stay, and patient satisfaction, were collected and compared between the two groups using statistical methods.Results: Patients in the ERAS-based nursing group exhibited significantly better outcomes compared to the standard care group. Postoperative complications, such as deep vein thrombosis and infections, were reduced (4.4% vs 11.7%, P< 0.05), and the average length of hospital stay was shorter (5.6 ± 1.8 days vs 8.3 ± 2.4 days, P< 0.001). Patient satisfaction scores were notably higher in the ERAS group (94.3% vs 78.6%, P< 0.001). Multivariate analysis identified perioperative nursing based on ERAS principles as an independent factor for improved recovery.Conclusion: Perioperative nursing care guided by ERAS principles significantly improves clinical outcomes in TKA patients, reducing complications and hospital stay while enhancing patient satisfaction. This study supports the broader implementation of ERAS protocols in perioperative nursing to optimize surgical care outcomes.Keywords: enhanced recovery after surgery, perioperative nursing, total knee arthroplasty, patient outcomes, complication reduction, early mobilization, pain management, nursing protocols